2017
DOI: 10.1007/s10439-017-1946-x
|View full text |Cite
|
Sign up to set email alerts
|

Using a Teaching Intervention and Calibrated Peer Review™ Diagnostics to Improve Visual Communication Skills

Abstract: Rice University’s bioengineering department incorporates written, oral, and visual communication instruction into its undergraduate curriculum to aid student learning and to prepare students to communicate their knowledge and discoveries precisely and persuasively. In a tissue culture lab course, we used a self- and peer-review tool called Calibrated Peer Review™ (CPR) to diagnose student learning gaps in visual communication skills on a poster assignment. We then designed an active learning intervention that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…During the teaching process of visual communication courses, the rendering of artistic style is particularly important. Different rendering methods will present different effects and different visual perceptions for the audiences ( Yang and Hsu, 2017 ; Saterbak et al, 2018 ). Therefore, the image style transfer network is designed through deep learning methods to provide better visual communication courses.…”
Section: Methodsmentioning
confidence: 99%
“…During the teaching process of visual communication courses, the rendering of artistic style is particularly important. Different rendering methods will present different effects and different visual perceptions for the audiences ( Yang and Hsu, 2017 ; Saterbak et al, 2018 ). Therefore, the image style transfer network is designed through deep learning methods to provide better visual communication courses.…”
Section: Methodsmentioning
confidence: 99%
“…Topping (2009) argues that this is an effective approach and encourages its use. Building on this guidance, some researchers have used Calibrated Peer Reviews (CPR) as guides for peer assessment, reporting progress in learning outcomes after its application and the strong instructor-peer correlation in overall grades (Furman & Robinson, 2003;Schneider, 2015;Saterbak et al, 2018;Suen, 2014). It is presented as a mechanism for learning evaluation (Saterbak et al, 2018) and an easily applicable approach to MOOC (Suen, 2014).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Building on this guidance, some researchers have used Calibrated Peer Reviews (CPR) as guides for peer assessment, reporting progress in learning outcomes after its application and the strong instructor-peer correlation in overall grades (Furman & Robinson, 2003;Schneider, 2015;Saterbak et al, 2018;Suen, 2014). It is presented as a mechanism for learning evaluation (Saterbak et al, 2018) and an easily applicable approach to MOOC (Suen, 2014). A study gives low or moderate quality feedback, and recommends it as "assessment for learning" rather than "assessment of learning" (Admiraal et al, 2014).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Empirical research-based justification for superior learning (n = 17) 1 "Numerous studies have demonstrated that students learn better when they are actively engaged in the learning processes (references)." [47] (p. 240) [13,39,41,47,48,51,52,[54][55][56]60,[62][63][64]75,81,85] Taken-for-granted justification for superior learning (n = 14) 1…”
Section: The Argument For Use Example Referencesmentioning
confidence: 99%
“…The problems seem easy when the instructor works them at the board; it is not until problems are assigned and students get stuck part way through or fail to complete them that real learning occurs." [48] (p. 188) [40,41,43,47,48,68,82,84,85] Learning theory (n = 8) 1…”
Section: The Argument For Use Example Referencesmentioning
confidence: 99%